Association of homozygous SDF-1 3′A genotype with proliferative diabetic retinopathy - Djuric, Zdenka; Sharei, Vahid; Rudofsky, Gottfried; Morcos, Michael; Li, Huiqing; Hammes, Hans-Peter; Nawroth, Peter Paul; Bierhaus, Angelika; Humpert, Per Magnus; Jonas, Jost B. (Acta diabetologica, 2010)
Stromal cell-derived factor 1 (SDF-1) is involved in the development of experimental proliferative retinopathy. Since little data are available on the genetic predisposition or on biomarkers predicting the development of proliferative retinopathy, we assessed the distribution of the SDF-1 3′A genotype in 130 diabetic patients with retinopathy. In patients with proliferative retinopathy, the frequency of the homozygous SDF-1 3′A genotype was significantly higher than in patients with non-proliferative retinopathy (10.9% of PDR vs. 0 of NPDR, P = 0.01). This association was confirmed when type 2 diabetes patients were analysed separately (10.3% of PDR vs. 0 of NPDR, P = 0.03). The finding that homozygous carriers of the SDF-1 3′A genotype are more frequent in diabetes patients with proliferative retinopathy suggests a possible role of this genotype in the development of sight-threatening diabetic retinopathy.
Published online: 21 April 2009
Gesehen am 06.02.2023